Academic Service Quality and Work Ethic: Their Effect on User Satisfaction at MTs Darul Huffaz Lampung - Malik, M. Adam; Nurhayati, Nurhayati (Journal of Advanced Islamic Educational Management, 2024)
The implementation of the education program at MTs Darul Huffaz Lampung is still developing to find a better form by paying attention to one of them, namely the quality of education to ensure the satisfaction of users of educational institution services. The objectives of this study are: to determine the effect of academic service quality (tangible, reliability, responsiveness, assurance, and empathy) and work ethic (hard work, discipline, honesty, responsibility and diligence) on user satisfaction at MTs Darul Huffaz Lampung. This type of research is descriptive quantitative to test the hypothesis between research variables. The population in this study were students and teachers at MTs Darul Huffaz as many as 460 respondents. The sampling technique in this study was purposive sampling technique. The sample in this study amounted to 82 respondents, so the response rate in this study was 65%. Data analysis techniques using regression analysis, both by using partial tests (t tests) and simultaneous tests (F tests) as well as the coefficient of determination test. The results showed that first, partially the indicators of academic service dimensions had a significant effect on user satisfaction.